Analisis Keluhan Gejala Neurotoksik pada Pekerja Industri Percetakan XYZ - Moch. Sahri; Nikhen Hanifah Alvianshah; Maya Nurahmadiana Syarifah; Muchamad Rafi Wahyu Pratama (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2022)
Indonesia has quite a number of business or industrial branches, one of which is a business that never subsides, namely the printing business. Currently technology is growing, the printing business in Indonesia that uses digital or offset machines continues to grow. The printing business is a type of business that is starting to be taken into account, especially in recent years the printing business has grown rapidly, seen from the small-scale printing industry that has recently emerged. Central nervous system damage can occur due to exposure to chemicals, especially those that are neurotoxic. Such as the use of neurotoxic drugs, as well as people who have metabolic disorders such as diabetes or uremia. Meanwhile, the focus of public health is the relationship between neurotoxic damage and toxic substances (toxins) found in the workplace. This research was conducted by means of field observations which aim to dig up information on complaints of neurotoxic symptoms in workers who work in the spatter industry. This research was conducted in one of the XYZ printing industries. XYZ printing company has 25 workers who are respondents in this study. Based on table 1 and table 2 regarding the distribution of answers to complaints of neurotoxic symptoms in respondents to XYZ printing workers, it is found that there are 5 (20%) positive respondents experiencing neurotoxic symptoms..